Influencia de la morbilidad y uso de recursos en pacientes que demandan atención por trastorno de ansiedad generalizada en el ámbito de la atención primaria de salud()() - Sicras-Mainar, Antoni (Aten Primaria, 2008)
OBJECTIVE: To evaluate the co-morbidity, health care use, economical impact, and availability of effective treatments used in generalised anxiety disorder (GAD) patients in a primary care setting (PCS). METHOD: A retrospective multicentre population-based study. SETTING: Five primary care clinics managed by Badalona Serveis Assistencials S.A., Barcelona, Spain. PARTICIPANTS: Outpatient records of patients over 18 years managed at 5 PCSs during 2006. Patients with and without GAD were compared. In GAD patients, 4 groups were established for comparison, according to pharmacological prescription. MEASUREMENTS: Main outcomes measures were general, reason/co-morbidity, health care use and primary care cost (visits, diagnostic/therapeutic tests, and drugs).We counted work absenteeism as an indirect cost. Pharmacological prescription was studied according to evidence-based recommendations and Spanish health-approved indications. The statistical analysis included a multivariate model: logistic regression, analysis of covariance (ANCOVA), P<.05. RESULTS: Of the 65 767 patients included, 4.6% (95% confidence interval [CI], 3.9-5.3) had GAD. Patients with/without GAD, the average episode/year was 6.1 versus 4.7 and attendance/year 10.0 versus 7.6; P<.001.GAD was associated with women (odds ratio [OR], 1.8), dyslipidemia (OR, 1.2), smoking (OR, 1.4), depression (OR, 1.2), and cerebrovascular accident (OR, 1.6) (P<.02). The mean direct cost/year adjusted by age, gender and morbidity load was €686 versus €557 (P<.001). GAD was associated with higher directs costs. The recommended treatment was followed in 40.1% of total patients (95% CI, 38.4-41.8). CONCLUSIONS: Patients with GAD have greater co-morbidity and higher direct costs in PCS. Means designed to improve the recognition and treatment of these patients should be established in the PCS.